Acute cellular rejection versus recurrent hepatitis C after liver transplantation: Clinical and pathological features driving a rational diagnostic approach. Issue 4 (2nd July 2014) - de la Peña‐Moral, Jesús M.; Pons, Jose A.; Tome, Santiago; Gude, Francisco; Miras, Manuel; Bermejo, Juan; Ramirez, Pablo; Berenguer, Marina; Varo, Evaristo; Forteza, Jeronimo; Parrilla, Pascual
<x xml:space="preserve">Abstract</x> Aim The aim of our study was develop and validate an algorithm system based on morphological features for finding the differences between recurrent hepatitis C virus (HCV) and acute cellular rejection (ACR) in liver biopsies of HCV‐transplanted patients. Methods Two hundred and eighty‐eight liver biopsies were analyzed from 121 patients transplanted for HCV. A diagnostic consensus was reached between clinicians and pathologists in 214 biopsies for the diagnosis of recurrent HCV or ACR. A random sample of 114 liver biopsies (derivation cohort) was taken to generate the diagnostic tree and was subsequently evaluated using the validation cohort in 100 liver biopsies by recursive partitioning analysis of morphological variables and time since transplantation. Results The presence of endotheliitis together with a time of less than 6 weeks since LT definitely excluded recurrent HCV. After obtaining the regression tree, diagnostic accuracy was 96% and 93% in the derivation and validation cohort, respectively. Both cases surpassed the pathologist's original diagnosis, which had a diagnostic accuracy of 91% (P < 0.05, for both comparisons). Conclusion A recursive partitioning analysis of the morphological features in liver biopsies from HCV‐transplanted patients may be useful for easily distinguishing between recurrent HCV and ACR.